Shear Strength Characterization of Bauxite Deposits in Kuantan, East Coast Malaysia - Noorul Iqhlima Najwa, I.; Haryati, Awang; Noram Irwan, Ramli; Putra Jaya, Ramadhansyah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Engineering characterization which are useful for "temperate" zone soils usually fail to predict the field performance of bauxitic soils, because the index tests upon which the characterization are based are not always reproducible for bauxitic soils. Fifteen (15) bauxitic soil of undisturbed and disturbed samples from 3 distinct sites in Kuantan, all derived from basalt parent rock but representing various stages of weathering were subjected to engineering and mineralogic tests. Values for cohesion and friction angles are evaluated. Soils from Semambu has the highest moisture content of 33.27%, the cohesion value is however lower compared to Bukit Goh which has moisture content of 21.74%. Study are further done to discover the relationship with cohesion and friction angles. Thus, by measuring the cohesion and friction angle can evaluate the performance of bauxite shear strength.